POLITIK SANTET: KONFLIK SOSIAL DAN PERAN PEMERINTAH KABUPATEN BANYUWANGI - Dimas Imaniar; Wisnu Ardytia (FKIP e-PROCEEDING, 2018)
Abstract: This writing examines how the form of conflict in Banyuwangi society happens? How is the effort of Banyuwangi regency government in dealing with the conflict? The analysis shows that the form of conflict not only occurs because the witchcraft in Banyuwangi civilization attaches and becomes a hereditary tradition, but also the actualization of the introvert attitude of the dominant Banyuwangi society to resolve problems in their own way and no one else knows. The handling that is done by the government based on the Banyuwangi Regency under law No. 7 of 2012 on: Social Conflict, as well as other regulations that are issued by the district government of Banyuwangi. The Effort that is done is early detection as conflict prevention, conflict termination by involving the related community leaders and the post-conflict recovery through reconciliation, rehabilitation and reconstruction. Key word: Conflict mapping and Banyuwangi regency government policy